2014
DOI: 10.1093/mnrasl/slu029
|View full text |Cite
|
Sign up to set email alerts
|

Identification of the progenitors of rich clusters and member galaxies in rapid formation at z > 2

Abstract: We present the results of near-infrared spectroscopy of Hα emitters (HAEs) associated with two protoclusters around radio galaxies (PKS1138-262 at z=2.2 and USS1558-003 at z=2.5) with Multi-Object Infrared Camera and Spectrograph (MOIRCS) on the Subaru telescope. Among the HAE candidates constructed from our narrow-band imaging, we have confirmed membership of 27 and 36 HAEs for the respective protoclusters, with a success rate of 70 per cent of our observed targets. The large number of spectroscopically confi… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
102
2
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 69 publications
(112 citation statements)
references
References 27 publications
7
102
2
1
Order By: Relevance
“…The inferred dynamical masses of the protocluster cores are consistent with being the typical progenitors of present-day most massive clusters (Shimakawa et al 2014a). Also, those HAEs in the protoclusters show much higher [Oiii]/Hβ ratios than local star forming galaxies.…”
supporting
confidence: 75%
“…The inferred dynamical masses of the protocluster cores are consistent with being the typical progenitors of present-day most massive clusters (Shimakawa et al 2014a). Also, those HAEs in the protoclusters show much higher [Oiii]/Hβ ratios than local star forming galaxies.…”
supporting
confidence: 75%
“…In the Millennium simulation, Chiang et al (2013) found that the first M ≥ 10 14 M halos are not present until z ≤ 2.3, and may not be virialized until a dynamical time later. However, there are some indications that subhalos in protoclusters can be virialized, as observed by Venemans et al (2007); Shimakawa et al (2014) and Topping et al (2016). These subhalos can be seen as bimodal distributions of protocluster galaxies along the LOS.…”
Section: Mass Estimatesmentioning
confidence: 89%
“…Because the average surface density of LBGs down to R = 25.5 is roughly 1-2 galaxies per square arcminute (Steidel et al 1999(Steidel et al , 2004, the process of observing LBGs for LyC emission is greatly streamlined by observing galaxy protoclusters, which have an increased density of objects at a particular redshift. Several galaxy protoclusters have already been identified in the literature at 2 < z < 4 (see, e.g., Kodama et al 2007;Venemans et al 2007;Hatch et al 2011;Cucciati et al 2014;Lemaux et al 2014;Shimakawa et al 2014;Diener et al 2015). At the rate of one LyC detection per protocluster, observations of at least ∼10 protoclusters would be necessary to obtain a sample large enough to investigate systematic differences between LyC-leakers and non-leakers.…”
Section: The Future Of Lyc Surveysmentioning
confidence: 97%